Diversity of Butterflies (Lepidoptera; Rhopalocera) in Three Habitat Types of Forest Edge Area of Bukit Mas Village, North Sumatra, Indonesia - Nurhayati; Husna, Fairuz; P.Patria, Mufti; Winarni, Nurul (Department of Forest Resources Conservation and Ecotourism - IPB University, 2025)
The limited information on butterfly responses to urbanization, particularly in Indonesia, prompted this study, which aims to assess butterfly diversity in different habitats (forest edge, residential areas, and community plantations) within the buffer zone of Gunung Leuser National Park, specifically in Bukit Mas Village, North Sumatra. Observations of plantation habitats were conducted in Aras Napal Hamlet, a buffer zone area, and Bukit Mas Village plantations. This exploratory study, conducted in September 2023, used the Point Count method with 18 points in residential and plantation habitats and 8 points in forest edge habitats. Each count point had a 5-meter radius with 10 minutes of observation, repeated twice daily (08.00–12.00 and 13.00–17.00), and the distance between points was 100 m. A total of 2,536 individuals from 89 species and seven families were recorded, with Nymphalidae being the most dominant family (44 species, 687 individuals). Extrapolation using the iNEXT package shows higher diversity in forest edge as well. At the same time, Residential areas provide a more diverse environment regarding species, while the Forest Edge exhibits the lowest diversity. This study highlights the importance of habitat heterogeneity in maintaining butterfly diversity in buffer zones affected by human activities. In conclusion, species diversity is highest in residential areas, followed by plantations, and lowest in forest edges.